Case report: A novel transcutaneous electrical nerve stimulation improves dysesthesias and motor behaviors after transverse myelitis - Nishi, Yuki; Ikuno, Koki; Minamikawa, Yuji; Osumi, Michihiro; Morioka, Shu (Frontiers in Human Neuroscience, 2024)
PurposeTransverse myelitis (TM)-associated dysesthesia is diverse and frequently resistant to treatment. This study explored the comprehensive effects of a novel transcutaneous electrical nerve stimulation (TENS) approach tailored to an individual’s specific dysesthesia profile in a patient with TM.Patient and methodA 52-year-old woman with severe dysesthesias in the left C8 sensory area caused by TM underwent an A-B-A-B-A design intervention. The baseline (phase A) and intervention (phase B) phases were both 7 days. Tingling and allodynia were scored on an 11-point numerical rating scale pre-, post-, and 1 h post-treatment. Upper limb activities during daily living were assessed using a wrist-worn accelerometer. The intervention phase consisted of 60-min sessions of TENS two times daily. Furthermore, the intervention and carry-over effects of TENS were evaluated using Tau-U and Bayesian unknown change point models.ResultsThe effects of TENS resulted in the immediate improvement in tingling, allodynia, and upper limb activity. Long-term effects of TENS affected tingling and upper limb activity; however, no impacts on allodynia were observed.ConclusionThis novel TENS approach shows promise as an effective treatment, even in rare and treatment-resistant dysesthesia associated with TM.